A qualitative study generating an item pool for a scale that measures negativity experienced by HIV/AIDS lay counsellors - Van der Westhuizen, Sune (Stellenbosch : University of Stellenbosch, 2010)
Digitized using a Konica Minolta 211 PCL scanner at 300 dpi.